Pendampingan Penyusunan Rekomendasi Kebijakan Penilaian Kinerja Berbasis Manajemen Pengetahuan Pada PT INKA (Persero) - Novianti, Khusnul Rofida; Widayat, Widayat; Roz, Kenny (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2022)
PT Industri Kereta Api or PT INKA (persero) is a State-Owned Enterprise (BUMN) that is a producer of land transportation, especially the first integrated train in Southeast Asia. In the continuous improvement process carried out by PT INKA, one important aspect is the change in the use of information systems in the performance appraisal process called Iknows (INKA Knowledge Management System). This system must be used as one of the conditions required in the Superior Performance Assessment Criteria (KPKU) process launched by the Ministry of SOEs. Related to the dynamics of internal changes in the company, in this case, a change in the knowledge management system (Knows), will more or less affect the situation, climate, and even the company's work culture. Ideally, changes that occur in the company are quickly followed by adjustments to existing human resources. However, not every change that is well-intentioned, so that the company is more advanced and developing gets a positive response from the existing human resources.